2018
DOI: 10.3390/v10070351
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Development to Bacteriophages Occurring during Bacteriophage Therapy

Abstract: Bacteriophage (phage) therapy, i.e., the use of viruses that infect bacteria as antimicrobial agents, is a promising alternative to conventional antibiotics. Indeed, resistance to antibiotics has become a major public health problem after decades of extensive usage. However, one of the main questions regarding phage therapy is the possible rapid emergence of phage-resistant bacterial variants, which could impede favourable treatment outcomes. Experimental data has shown that phage-resistant variants occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
333
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 410 publications
(350 citation statements)
references
References 113 publications
(145 reference statements)
13
333
1
3
Order By: Relevance
“…Nevertheless, an increased phage resistance causes a reduced competitive bacterial fitness to the environment . As phage resistance requires many resources, mutation that result in phage resistance can cause other mutations related to bacterial fitness . Hall et al reported that bacteria possessing a broad range of phage resistance had a lower fitness as compared with the phage‐susceptible bacterial population .…”
Section: The Effect Of Bacterial Evolutionary Changes On the Developmmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an increased phage resistance causes a reduced competitive bacterial fitness to the environment . As phage resistance requires many resources, mutation that result in phage resistance can cause other mutations related to bacterial fitness . Hall et al reported that bacteria possessing a broad range of phage resistance had a lower fitness as compared with the phage‐susceptible bacterial population .…”
Section: The Effect Of Bacterial Evolutionary Changes On the Developmmentioning
confidence: 99%
“…Reduction of fitness includes reduced growth rate and loss of important surface features necessary for bacterial virulence . Thus, phage resistance is suggested to be unfavourable to bacteria themselves and in contrary, phage‐driven adaptation might be beneficial for the bacteria . Furthermore, phage resistance in bacteria is believed to be a temporary process.…”
Section: The Effect Of Bacterial Evolutionary Changes On the Developmmentioning
confidence: 99%
“…Nevertheless, bacteriophages are easily transmitted from person to person, demonstrated by data showing that substantial numbers of gut and oral bacteriophages are shared amongst genetically unrelated, cohabitating individuals . Finally, therapeutic use of bacteriophages to attack pathogens selectively within biofilm communities has been suggested . This approach is not without its problems because in early bacteriophage therapy trials, the emergence of pathogens resistant to bacteriophage attacks has been demonstrated .…”
Section: Future Challengesmentioning
confidence: 99%
“…). Resistance to phages commonly evolves when bacteria are cultured in vitro , but few studies have investigated phage resistance evolution within natural bacterial hosts such as plants or animals (Oechslin ).…”
mentioning
confidence: 99%
“…vitro, but few studies have investigated phage resistance evolution within natural bacterial hosts such as plants or animals (Oechslin 2018).…”
mentioning
confidence: 99%